Las 5´s y el Modelo Kaizen en Función del Servicio al Cliente en el Negocio Servicios Profesionales Múltiples de la ciudad de Babahoyo - Moncada Palma, Jimmy Enrique (2017)
The business Professional Services Múltiples started its activities on October 15, 1999 in the city of Babahoyo, its main economic activity is to provide accounting and tax advice, bookkeeping, natural and legal persons, also offers banking services such as retirement, deposits, account opening, also offers cyber services and sale of school supplies.